Spiritualitas Misional Gereja dalam Krisis Ekologi menurut Markus 16:15 dan Thomas Berry - Agasta, Ferialdi; Raya, Uci (STT Bala Keselamatan Palu, 2024)
Abstract: The problem of the Christian mission, and indeed the problem of all humanity in this age, is to recover the Earth from the ecological crisis, the effects of which are already being felt. But among the billions of people in the world, only a few are aware of this crisis and are working to prevent it from getting worse. But the reality is that the mission of the church is still far from this effort. This is evidenced by the fact that most church leaders in Sunday worship sermons rarely touch the awareness of their congregation members in applying ecological missional spirituality in their lives. This article aims to restore ecological missional spirituality to direct Christians and all humanity to care about the ecological crisis. The method used in this study is a qualitative method with a literature study, namely collecting all data sourced from books and previous studies related to this study. This study found that the church's missional spirituality should touch the awareness of all humans that all of God's creations have an integral relationship. For this reason, the church must be at the forefront in inviting other human communities to realize the integral relationship in all of creation, and to collaborate with all human communities to restore the earth from the ecological crisis. Abstrak: Persoalan misi kristen, dan tentu saja persoalan seluruh umat manusia di zaman ini ialah mengupayakan Bumi ini pulih dari krisis Ekologi yang dampaknya sudah makin terasa. Tetapi di antara miliaran manusia yang ada di dunia ini hanya sedikit saja yang menyadari dan turut mengupayakan agar krisis ini tidak menjadi semakin parah. Tetapi kenyataannya misi kristen masih jauh dari upaya ini. Ini dibuktikan kebanyakan pemimpin-pemimpin gereja dalam khotbah peribadatan hari minggu masih jarang menyentuh kesadaran anggota jemaatnya dalam menerapkan spiritualitas misional ekologis dalam kehidupan mereka. Artikel ini bertujuan untuk memulihkan spiritualitas-misional ekologis untuk mengarahkan umat Kristen dan seluruh umat manusia peduli pada krisis ekologis. Metode yang digunakan dalam kajian ini ialah metode kualitatif dengan studi pustaka yaitu mengumpulkan seluruh data-data yang bersumber dari buku-buku dan penelitian-penelitian sebelumnya yang sekaitan dengan kajian ini. Penelitian ini menemukan bahwa spiritualitas-misional gereja harusnya menyentuh kesadaran semua manusia bahwa seluruh ciptaan Tuhan memiliki hubungan yang integral. Untuk itu, gereja harus menjadi garda terdepan dalam mengajak komunitas manusia lain menyadari hubungan integral dalam seluruh ciptaan, dan merajut kerjasama dengan seluruh komunitas manusia untuk memulihkan bumi dari krisis ekologis.